Electrospinning of n-hemin/PAN Nanocomposite Membranes and Its Photo-Enhanced Enzyme-like Catalysis - Han, Xu; Tao, Yun; Xu, Chao; Deng, Yicong; Meng, Zisen; Dou, Zhenhao; Wang, Peng; Feng, Quan (Polymers, 2022)
Hemin possesses great potential in eliminating organic pollutants due to its mild reaction condition, light-harvesting efficiency, and environmental friendliness. However, it has drawbacks such as being easy to aggregate and hard to recycle, and poor stability should be improved in practical application. Herein, the subject developed an electrospinning approach to enable the hemin particulates to be immobilized onto polyacrylonitrile (PAN) nanofibers stably. Hydrogen peroxide (H2O2) was adopted as an oxidant in the system to simulate the enzymatic catalysis of hemin in an organism. Scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), UV-Vis diffuse reflection spectroscopy (DRS), and electron spin resonance spectroscopy (ESR) analysis was employed to discuss the morphology, structure, and mechanism of the prepared n-hemin/PAN nanocomposite membranes, and 0.02 mmol L−1 of the rhodamine B (RhB) removal activity in different conditions was also verified with these membranes. The kinetic studies showed that n-hemin/PAN nanocomposite membranes maintained excellent properties both in adsorption and degradation. Around 42% RhB could be adsorbed in the dark, while 91% RhB decolorized under xenon lamp irradiation in 110 min, suggesting the catalytic performance of n-hemin/PAN was greatly driven by light irradiation. Differing from the axial coordinated hemin complexes, n-hemin/PAN would catalyze hydrogen peroxide into •OH radicals rather than •OOH and high-valent metal-oxo species. This work provides an effective way to support hemin as nanocomposite membranes, in which the molecular interaction between polymer and hemin made their light adsorption an obvious red shift.